Handbook of organizational learning and knowledge management - Easterby-Smith, Mark.; Lyles, Marjorie A. (Chichester, West Sussex : Wiley, 2011)
'The fully revised and updated version of this successful Handbook is welcomed by management scholars world-wide. By bringing together the latest approaches from the leading experts in organizational learning & knowledge management the volume provides a unique and valuable overview of current thinking about how organizations accumulate'knowledge' and learn from experience.Key areas of update in the new edition are:[bullet] Resource based view of the firm[bullet] Capability management[bullet] Global management[bullet] Organizational culture[bullet] Mergers & acquisitions[bullet] Strategic management[bullet] Leadership'--
Originally published under title : Blackwell handbook of organizational learning and knowledge management, 2003.
Includes bibliographical references and index.
Keywords: Organizational learning -- Handbooks, manuals, etc; Knowledge management -- Handbooks, manuals, etc